Amoebiasis in Iran: a systematic review and meta-analysis. Issue 15 (11th July 2018) - Haghighi, Ali; Riahi, Seyed Mohammad; Taghipour, Ali; Spotin, Adel; Javanian, Mostafa; Mohammadi, Mohsen; Esmaeili Dooki, Mohammadreza; Rostami, Ali
Abstract: A comprehensive meta-analysis study was performed to estimate the reliable national prevalence and molecular epidemiology of amoebiasis in Iran. Nine English and Persian databases were searched to achieve the relevant studies. Pooled estimates were generated and meta-regression was performed. We identified 71 eligible articles involving 330 930 subjects from 25 provinces to be included in the final analysis. Moreover, 17 studies compromising 462 polymerase chain reaction (PCR)-positive isolates performed molecular analysis to inter-species differentiation. The pooled prevalence of Entamoeba infection among Iranian population was about 1% (95% CI 0.8–2.0%). Moreover, regarding Human Development Index (HDI), a higher prevalence was observed in undeveloped provinces. Out of 462 PCR-positive isolates, 83% (95% CI 69–94%) and 12% (95% CI 3–24%) were Entamoeba dispar, Entamoeba histolytica, respectively. In subgroup analysis based on molecular results, in general, population prevalence of Entamoeba dispar and E. histolytica were 91% (95% CI 80–99%) and 7%, (95% CI 0–19%), respectively, while prevalence of these species in patients with gastrointestinal disorders were 75% (95% CI 45–96%) and 18% (95% CI 1–43%), respectively. Our findings indicate the low burden of amoebiasis in Iran. E. dispar, that is mostly non-pathogenic, was identified as most prevalent species. Nevertheless, we suggest more public health interventions in areas with lower HDI.